Water and the landscape : a Landscape architecture book - Clay, Grady (New York : McGraw Hill Education, 1979)
It was no accident that in a national design competition for landscape architects in the 1970s, the jury chose among 18 winning projects 11 having to do with water-related development of the landscape. It was no accident that the world's first desertification conference was held by the United nations in Nairobi.
1. Watershed planning and design -- 2. Communities and rivers -- 3. Low-lying land development -- 4. Hazards -- 5. Resource analysis and management -- 6. Recreational water use.
Includes index.
Keywords: LANDSCAPE DESIGN -- USE OF WATER